2019
DOI: 10.1021/acssensors.9b00377
|View full text |Cite
|
Sign up to set email alerts
|

Resonant Plasmonic Nanoslits Enable in Vitro Observation of Single-Monolayer Collagen-Peptide Dynamics

Abstract: Proteins perform a variety of essential functions in living cells and thus are of critical interest for drug delivery as well as disease biomarkers. The different functions are derived from a hugely diverse set of structures, fueling interest in their conformational states. Surface-enhanced infrared absorption spectroscopy has been utilized to detect and discriminate protein monomers. As an important step forward, we are investigating collagen peptides consisting of  a  triple helix. While they constitute the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 55 publications
0
17
0
Order By: Relevance
“…[3,4] They are classified based on the method adopted for sensing, including optical, [5][6][7][8] electrochemical, [9,10] electrical, [11] thermometric, [12] mass sensitive, [13] magnetic [14][15][16] etc. They can also be classified based on the type of analyte into different types, including pH electrodes [17] and sensors for metal ions and determining gases, [18][19][20] as well as the mode of application into in vivo [21] and in vitro [22] sensors for process monitoring. Among these methods, electrochemical methods possess remarkable features, such as high sensitivity, short response time, low cost, simplicity of instrumentation, the possibility of miniaturization, and integration with portable devices.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[3,4] They are classified based on the method adopted for sensing, including optical, [5][6][7][8] electrochemical, [9,10] electrical, [11] thermometric, [12] mass sensitive, [13] magnetic [14][15][16] etc. They can also be classified based on the type of analyte into different types, including pH electrodes [17] and sensors for metal ions and determining gases, [18][19][20] as well as the mode of application into in vivo [21] and in vitro [22] sensors for process monitoring. Among these methods, electrochemical methods possess remarkable features, such as high sensitivity, short response time, low cost, simplicity of instrumentation, the possibility of miniaturization, and integration with portable devices.…”
Section: Introductionmentioning
confidence: 99%
“…They are classified based on the method adopted for sensing, including optical, [5–8] electrochemical, [9,10] electrical, [11] thermometric, [12] mass sensitive, [13] magnetic [14–16] etc. They can also be classified based on the type of analyte into different types, including pH electrodes [17] and sensors for metal ions and determining gases, [18–20] as well as the mode of application into in vivo [21] and in vitro [22] sensors for process monitoring.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, it is also well known that so-called inverse nanostructures, consisting of slits fabricated in a continuous metallic film, also feature sharp, tunable resonances over the whole mid-IR spectral range. It was recently found that the measured average SEIRA signal of slits is higher compared to their inverse rod structures for the same vibrational layer, showing their advantages for SEIRA experiments over the better-known solid nanoantennas [7,8]. Moreover, slits present yet another advantage with respect to rods which makes them best suited for the present work: the gold surface surrounding the slits remains conducting and allows combining SEIRA with electrochemical measurements, which is of great interest to study redox proteins [9,10].…”
Section: Introductionmentioning
confidence: 92%
“…For example, Semenyshyn et al developed a Au plasmonic nanoslit device to monitor and better understand collagen protein folding dynamics. [199] In another example, Seo et al developed a nanoslit array with controlled evaporationdriven transport of small molecules in gas permeable, lowaspect ratio nanoslits that can be used to model and understand fluid transport in other systems. [150]…”
Section: Nanoslitsmentioning
confidence: 99%